Korean cuisine: centuries-old tradition at the forefront (2014)
The following document seeks to introduce basic information about Korean cuisine and how its oldest expressions have gained great relevance on the world stage today, starting from the history of Korea's most characteristic culinary elements and how they took on the importance they currently have. Finally, Kimchi is highlighted as a reference to show the possibility that a nation has to take privileged positions outside its national borders using its food culture as a tool for that purpose. It concludes with an invitation to the reader to explore the cultural union between Korea and Latin America through its kitchens.